Rapid identification of polymorphic sequences in non‐model fungal species: the PHYLORPH method tested in Armillaria species. Issue 4 (12th January 2016) - Dutech, C.; Prospero, S.; Heinzelmann, R.; Fabreguettes, O.; Feau, N.
Summary: Development of molecular markers for phylogenetic, population genetics and phylogeographic studies remains arduous in non‐model species with low or no genomic resources. Sequencing the whole or a large part of the genome of the target species using next‐generation sequencing technologies is considered a promising method, although it still needs a large investment in bioinformatics. To quickly find polymorphic markers in fungal species, we tested an alternative method, named PHYLORPH. This method allows users to quickly target polymorphic regions of single copy genes in fungi using public databases. We applied this method to Armillaria species, which are important fungal pathogens and saprophytes playing a central role in the dynamics of forest ecosystems worldwide. We isolated 32 single copy genes with numerous single nucleotide polymorphism (SNP) sites. A genetic analysis of two French populations validated the polymorphism of 80 among 92 SNPs tested, and seven of these sequences exactly reconstructed the known phylogenetic tree of four tested Armillaria species. These results confirmed that the PHYLORPH method is efficient to identify various markers at both the intra‐ and interspecific levels for fungal species with no or few previous genetic markers.